The influence of gait and speed on the dynamic navicular drop – A cross sectional study on healthy subjects. (September 2018) - Pohl, J.; Jaspers, T.; Ferraro, M.; Krause, F.; Baur, H.; Eichelberger, P.
Highlights: Implementation of a 4-marker foot model to evaluate dynamic navicular drop (dND). Magnitudes of static dND are not reflected in dynamic dND measures. The gait style, running or walking, has a large effect on the dND. Increasing dND in running and decreasing dND in walking for increasing gait speed. Abstract: Introduction: Variations of gait speed influence kinematic variables that may have an effect on dynamic foot deformation. The influence of gait speed on the navicular drop has not yet been investigated. Methods: The navicular drop was evaluated in static and dynamic conditions using a 3D-motion capture system. The dynamic navicular drop was evaluated on a treadmill while walking and running at three different speeds. A repeated measures ANOVA and post-hoc tests were conducted to evaluate the differences in dynamic navicular drop, corresponding unloaded navicular height at foot strike and loaded navicular height during stance. Results: Higher walking speed led to a significant decrease in navicular height at foot strike and a subsequent decrease of dynamic navicular drop ( p  = 0.006). Across increasing running speeds, minimum navicular height was significantly decreased which in consequence led to an increased dynamic navicular drop ( p  = 0.015). For walking and running at the same speed, there was a large effect of gait style with an increase of dynamic navicular drop by 3.5 mm ( p  < 0.001) during running. Discussion: The change of gait from walking to running at the same speed had a large effect on dynamic navicular drop. The values of navicular height at foot strike and minimum navicular height during stance should be taken into account for the interpretation of dynamic navicular drop measures. Static and dynamic navicular drop measures differ substantially.